Analysis of Fuel Efficiency and Speed Increase on Ferry MV BATAM FAST 20 (High Speed Craft) through the Installation of a Hull Vane - Ardiansyah, Angga Andi; Suwasono, Bagiyo; Awwalin, Rodlitul (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2026)
This study investigates the impact of Hull Vane System installation on fuel efficiency and speed enhancement for High Speed Craft (HSC) ferries, focusing on MV. Batam Fast 20 operating on the Batam–Singapore route. The Hull Vane, a fixed hydrofoil mounted at the stern below the waterline, is designed to reduce hydrodynamic resistance and improve vessel performance. Numerical simulations using Computational Fluid Dynamics (CFD) with RANSE-based solvers were conducted across various speeds (10–25 knots) and foil attack angles (0°, 2°, 4°,6°). Results indicate that Hull Vane offers significant drag reduction only at low speeds (10 knots), achieving up to 26.99% resistance reduction. However, at operational speeds (20–25 knots), the system increases resistance due to excessive lift, causing bow trim and higher wetted surface area. Validation was performed through grid independence studies and comparison with experimental data and Maxsurf Resistance software. The findings conclude that Hull Vane System is unsuitable for MV. Batam Fast 20 due to its hull geometry and waterjet configuration. The study recommends exploring alternative technologies such as bow foils or automated trim control systems for high-speed vessels, emphasizing the need for adaptive hydrodynamic solutions in modern ferry operations.